Human Factors on Fire Hazards: A Correlation Study in a Vocational Education Environment - Wildan Nugraha; Minulya Eska Nugraha; Sutiyo Sutiyo; Oke Hendra (International Journal of Educational Review, 2023)
A fire disaster is one of the disasters that can harm many parties. The danger of fire can result in several threats to safety and property and can often even result in loss of life. There are various things that can start fires, namely human, equipment, and natural factors. The purpose of this study is to ascertain how human variables and fire dangers are related in vocational education environments. Negligence is a fundamental characteristic that cannot be prevented, but this can be minimized by knowing the causes of fires and steps that can be taken to reduce the potential danger of fires caused by human factors. This study includes a cross-sectional study design, a quantitative technique, and a correlational descriptive method. Data was collected by distributing questionnaires, as well as making observations as data to strengthen the results of questionnaire data analysis. The variables used in this research are Fire Fighting Knowledge (X1), Fire Incident Experience (X2), and Fire Fighting Behavior (Y). The study's findings indicate that knowledge and fire prevention behavior are significantly correlated, as are experience and fire prevention behavior, and that knowledge and experience are significantly correlated with fire prevention behavior.